2017
DOI: 10.1002/cphc.201600834
|View full text |Cite
|
Sign up to set email alerts
|

Creating Honeycomb Structures in Porous Polymers by Osmotic Transport

Abstract: Understanding why honeycombs are shaped the way they are has moved biologists, physicists, chemists, and mathematicians alike. It was only recently that the honeycombs' shape "at birth" was included in the ongoing discussions: at birth, the cells are spherical but then transform into the well-known hexagons. It was proposed that a flow of wax-driven by surface tension effects-is the reason for this transformation. Our recent work on synthetic polymer foams with honeycomb-like structures points towards a very d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 14 publications
3
26
0
2
Order By: Relevance
“…The monodisperse foams follow the model by Gibson and Ashby, [31] while the value for the graded foam is lower than predicted by the model. (left) Normalized Young's modulus of polystyrene foams synthesized via foamed emulsion templating plotted against the relative density.…”
supporting
confidence: 56%
“…The monodisperse foams follow the model by Gibson and Ashby, [31] while the value for the graded foam is lower than predicted by the model. (left) Normalized Young's modulus of polystyrene foams synthesized via foamed emulsion templating plotted against the relative density.…”
supporting
confidence: 56%
“…Chemie statement of Williams et al [30,31] An approach for the production of monodisperse polystyrene foams was presented by Quell et al [9,38,40,41] In these studies,m onodisperse waterin-styrene emulsions were generated by means of am icrofluidic device.T he resulting template was then polymerised and am onodisperse polystyrene foam was obtained. It was shown that the shape of the pores (polyhedral or spherical) can be controlled by the locus of initiation of the polymerisation [38] and that an additional porosity within the pore walls can be produced by initiating the polymerisation within the continuous organic phase.…”
Section: Methodsmentioning
confidence: 99%
“…Außerdem berichteten sie,d ass das Styrol-zu-DVB-Verhältnis und die Te nsidkonzentration die Porengrçße beeinflussen. [9,38,40,41] In diesen Untersuchungen wurden monodisperse Wasser-in-Styrol-Emulsionen mithilfe der Mikrofluidik gebildet. [4]).…”
Section: Die Parameter Zur Feineinstellung Und Ihre Bedeutungunclassified
“…Ein Wegz ur Herstellung monodisperser Polystyrolschäume wurde von Quell et al vorgestellt. [9,38,40,41] In diesen Untersuchungen wurden monodisperse Wasser-in-Styrol-Emulsionen mithilfe der Mikrofluidik gebildet. Das hieraus resultierende Te mplat wurde anschließend polymerisiert, und man erhielt einen monodispersen Polystyrolschaum.…”
Section: Die Parameter Zurunclassified